2019
DOI: 10.1002/pcr2.10072
|View full text |Cite
|
Sign up to set email alerts
|

The structure transformation of pre‐oriented polylactic acid film during uniaxial stretching at room temperature

Abstract: In this article, the pre‐oriented polylactide (PLA) films were prepared by extrusion casting under melt‐stretching flow and cast roll temperature field. Shish‐kebab like structure was induced and the elongation at break under room temperature of PLA film prepared with melt‐draw ratio of 40 was high to 270%. To clarify the origin of this ductile behavior, the pre‐oriented PLA structure evolution during stretching at room temperature was followed. It was found that melt‐stretching makes the chains fully extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In PLA different approaches have been proposed to follow the evolution of the RAF by MTÀ DSC, from isothermal and nonÀ isothermal crystallization conditions [72], but none has referred to this event. However, in several studies regarding oriented PLA [73,74], it has been suggested that the organization of RAF could lead to mesophase, which is observable from calorimetric techniques. Although the macromolecules are not oriented in the scÀ PLAs studied there, the endothermic thermal event might be the signature of a fraction exhibiting intermediate degree of ordering between RAF and mesophase.…”
Section: Impact Of the Annealing On The Amorphous Fractions Charactermentioning
confidence: 99%
“…In PLA different approaches have been proposed to follow the evolution of the RAF by MTÀ DSC, from isothermal and nonÀ isothermal crystallization conditions [72], but none has referred to this event. However, in several studies regarding oriented PLA [73,74], it has been suggested that the organization of RAF could lead to mesophase, which is observable from calorimetric techniques. Although the macromolecules are not oriented in the scÀ PLAs studied there, the endothermic thermal event might be the signature of a fraction exhibiting intermediate degree of ordering between RAF and mesophase.…”
Section: Impact Of the Annealing On The Amorphous Fractions Charactermentioning
confidence: 99%
“…The restriction of the MAF was related to the intraoriented structure. 54 Additionally, the stretching could increase the tightness of RAF chains. The derivative of the complex heat capacity (C p ″) peaks of PLA films in the hydrolysis at 0 and 24 h is shown in Figure S5, Supporting Information, which became flat and broader due to the increase of crystallinity and degrading of amorphous chains after hydrolysis.…”
Section: Resultsmentioning
confidence: 81%
“…This diffraction peak could refer to the other disordered forms of α, previously reported as α′′ form by Marubayashi et al 52 and as α′ (δ) form by Takasaki et al, 53 which has loose chain packing and lower crystal density compared with the α form. Xu et al 54 also reported that the broad dispersing diffraction peak could be obtained from the small and dispersed crystals in the film structures. These small crystals were crystallized through a transformation of the mesophase and confined in the chain network during the melt-stretching crystallization.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The improvements of tensile strength and elongation at break for pre-stretched PLA films have been proved. 23,24,37 In this work, the impact strength of PLA materials is particularly focused. Figure 1B demonstrates the change of notched Izod impact strength with pre-strain for PLA/PCL 95/5 blend.…”
Section: ■ Results and Discussionmentioning
confidence: 99%